2021
DOI: 10.3389/fphar.2021.631100
|View full text |Cite
|
Sign up to set email alerts
|

A New Therapeutic Candidate for Cardiovascular Diseases: Berberine

Abstract: Cardiovascular diseases (CVD) are the leading cause of death in the world. However, due to the limited effectiveness and potential adverse effects of current treatments, the long-term prognosis of CVD patients is still discouraging. In recent years, several studies have found that berberine (BBR) has broad application prospects in the prevention and treatment of CVD. Due to its effectiveness and safety for gastroenteritis and diarrhea caused by bacterial infections, BBR has been widely used in China and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 111 publications
(139 reference statements)
0
37
0
Order By: Relevance
“…BBR has a wide range of pharmacological and therapeutic effects, and BBR has been widely used for its antimicrobial and antiprotozoal activities ( 2 ). Recently, as research continues, BBR has also been found to play a role in mood disorders ( 3 ), high blood pressure ( 4 ), hypercholesterolemia ( 5 ), hyperlipidemia ( 5 ), diabetes ( 6 ), heart failure ( 7 ), colorectal cancer ( 8 ), and other diseases. Because of its many effects, BBR is as commonly used as are aspirin and metformin.…”
Section: Introductionmentioning
confidence: 99%
“…BBR has a wide range of pharmacological and therapeutic effects, and BBR has been widely used for its antimicrobial and antiprotozoal activities ( 2 ). Recently, as research continues, BBR has also been found to play a role in mood disorders ( 3 ), high blood pressure ( 4 ), hypercholesterolemia ( 5 ), hyperlipidemia ( 5 ), diabetes ( 6 ), heart failure ( 7 ), colorectal cancer ( 8 ), and other diseases. Because of its many effects, BBR is as commonly used as are aspirin and metformin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that probiotics can influence the lipid metabolism and effectively alleviate atherosclerosis by means of regulating gut microbiota to reduce TMAO ( Liang et al, 2020 ). As a promising therapeutic candidate for CVD, performing in a somewhat similar way like probiotics but not like antibiotics, berberine has exhibited its pharmacological effects on modulating dysmetabolism and atherosclerosis experimentally and clinically though its poor bioavailability is also perceived ( Liu et al, 2016 ; Cao and Su, 2019 ; Cai et al, 2021 ). The possible explanation is that berberine displays its antiatherogenic properties via the active interaction with gut microbiota.…”
Section: The Interaction Between Berberine and Intestinal Microbiotamentioning
confidence: 99%
“…Berberine has been recognized as a pivotal therapeutic candidate for CVD because of its pleiotropic effects on modulating oxidative stress and inflammation related atherosclerosis ( Cai et al, 2021 ). It has been proved that berberine interrupts atherosclerosis via manipulating gut microbiota compositions and functional metabolites ( Wang et al, 2017 ; Agus et al, 2021 ), and meanwhile gut microbiota transforms berberine into intestinal absorbable form ( Feng et al, 2015 ; Feng et al, 2018b ).…”
Section: Insights Of Berberine Into the Gut-heart Axismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the role of BBR in the prevention and treatment of ASCVD is drawing increasing attention ( Cai et al, 2021 ). In the present study, we found that BBR treatment lowered the blood pressure and ameliorated the vascular dysfunction and pathological remodeling in the Ang II-induced mice.…”
Section: Discussionmentioning
confidence: 99%